The smARTS_Museum_V1: An open hardware device for remote monitoring of Cultural Heritage indoor environments. (October 2018) - Gaudenzi Asinelli, Mainardo; Serra Serra, Moisès; Molera Marimòn, Judit; Serra Espaulella, Jordi
Graphical abstract: Abstract: This paper presents an easy-to-use, easy-to-customize, and low cost device for remote monitoring of Cultural Heritage environments such as museums, art galleries, and historical archives. The prototype allows measurements of temperature, relative humidity, and dew point. The chip used is an ESP8266 characterized by on-board Wi-Fi. The hardware design is flexible in order to host extra sensors via I 2 C bus and easy replacement of microcontroller and sensors in the event of either malfunctions or substitution with newer versions. The device is programmable using the Arduino IDE. The data are sent to an IoT platform that allows real-time visualization, analyses, and download. Tests were performed in laboratory and at the Casa de Convalescencia in Vic (Spain), by monitoring the microenvironment of an exhibition cabinet hosting 18th century ceramics. The results achieved are promising: the open hardware and software approach allows plan further implementations and provides a solid base for device customizations; in terms of technology applied to Cultural Heritage, the implementation of open hardware does not only can lower significantly the costs, but also provides scientifically reliable alternatives to off the shelf technology, as well as enhances end-users capability to develop customized devices that can better address specific needs.